REPRESENTING POSTFEMINIST FEMALE CHARACTERS IN THE CONTEMPORARY MEDIASCAPE: THE DISCURSIVE FUNCTION OF IRONY - Virdis, Daniela Francesca Francesca (Verbum, 2018)
Addressing the interdisciplinary area of language & gender as applied to television and media studies, this article summarises the detailed analysis of some extremely popular contemporary TV series and media. With all their specificities, these significant cultural products share a reinvention of the codes of romance, by representing an up-to-date, somehow fashionable version of the traditional, and traditionally female, genre of romance geared to postfeminist consumer culture. The femininities and sexualities enacted in these cultural narratives may appear to be unsparingly and humorously critical of conventionally female linguistic and cultural stereotypes, and could therefore be regarded as radical feminist embodiments. Nevertheless, by means of an ironic and hyperbolic approach, they are in fact not only romantic and mainstream, but also ideologically biased, preserving a normative heterosexual white middle-class status quo, and restoring a patriarchal value system. A close critical scrutiny thus shows the stylistic and discursive strategies by which feminism has switched to postfeminist romance, and has thereby yielded to postfeminist backlash.